PEMANFAATAN MODAL SOSIAL PAULINA HANING BULLU PADA PILKADA DI KABUPATEN ROTE NDAO TAHUN 2018 - Anastresia Mite; Mudiyati Rahmatunnisa; Sri Zul Chaeriyah (JANE - Jurnal Administrasi Negara, 2022)
Paulina Haning Bullu's victory in the people of Rote Ndao Regency through the use of social networks in the form of relationships that have been built for a long time in the Rote Ndao community, social norms where closeness to traditional leaders and trust are due to interactions with the Rote Ndao community. The purpose of this paper is to find out and analyze the use of social capital, namely social networks, social norms and beliefs that are owned and utilized by Paulina Haning Bullu so that she can win the Regional Head Election in Rote Ndao Regency in 2018. This research method uses descriptive qualitative methods, data collection techniques used used through interviews (interviews) and documentation. In the analysis used is social capital, namely social networks, social norms and trust by Robert Putnam. Based on the results of this paper, it shows that Paulina Haning Bullu has succeeded in utilizing her social capital so as to lead to victory by getting the most votes in the regional elections in Rote Ndao Regency in 2018. Paulina Haning Bullu uses social capital, namely social networks, social norms and trust. Paulina Haning Bullu's approach to social networking builds relationships between social communities and religious communities and establishes good and ongoing relationships with the maintenance of intense communication in the community, namely PKK women, members of the Pelita Nee church. Social norms can be built because of their closeness to the Maneleo indigenous community, which is seen from the assessment of the candidate's behavior and belief in the positive impact of social networks and social norms where the interaction carried out is in the form of socializing the Paulina Haning Bullu campaign with the people of Rote Ndao Regency. Kemenangan Paulina Haning Bullu di masyarakat Kabupaten Rote Ndao melalui pemanfaatan jaringan sosial berupa relasi yang dibangun cukup lama di masyarakat Rote Ndao, norma sosial dimana kedekatan dengan tokoh adat dan kepercaayan karena adanya interaksi dengan masyarakat Rote Ndao. Adapun tujuan penulisan ini adalah mengetahui dan menganalisis pemanfaatan modal sosial yakni jaringan sosial, norma sosial dan kepercayaan yang dimiliki dan dimanfaatkan Paulina Haning Bullu sehingga dapat memenangkan Pilkada di Kabupaten Rote Ndao tahun 2018. Metode penelitian ini menggunakan metode kualitatif deskriptif, teknik penggumpulan data yang digunakan melalui wawancara (interview) dan dokumentasi. Pada analisis yang digunakan adalah modal sosial yakni jaringan sosial, norma sosial dan kepercayaan oleh Robert Putnam.Berdasarkan hasil penulisan ini menunjukkan bahwa Paulina Haning Bullu sukses memanfaatkan modal sosial yang dimilikinya sehingga mengantarkan kemenangan dengan mendapatkan suara terbanyak pada Pilkada di Kabupaten Rote Ndao tahun 2018. Paulina Haning Bullu menggunakan pemanfaatan modal sosial yakni jaringan sosial, norma sosial dan kepercayaan. Paulina Haning Bullu pada pendekatan jaringan sosial membangun relasi antara komunitas sosial dan komunitas agama dan terjalinlah hubungan-hubungan yang baik serta berlanjut terus-menerus dengan terpeliharanya komunikasi yang intens di masyarakat yakni para ibu-ibu PKK, jemaat gereja Pelita Nee. Norma sosial dapat terbangun karena adanya kedekatan dengan masyarakat adat  Maneleo yakni dilihat dari penilaian figur dari kandidat dalam berperilaku dan kepercayaan adanya dampak positif dari jaringan sosial dan norma sosial dimana interaksi yang dijalankan berupa sosialisasi pada kampanye Paulina Haning Bullu dengan masyarakat Kabupaten Rote Ndao.